Dynamics of soil and canopy temperature: a conceptual approach for Alentejo vineyards - Costa, J.M. (2022)
Context and purpose of the study - Climate change imposes increasing restrictions and risks to Mediterranean viticulture. Extreme heat and drought stress events are becoming more frequent which puts in risk sustainability of Mediterranean viticulture. Moreover row crops e.g. grapevine for wine, are increasingly prone to the impact of more intense/longer exposure time to heat stress. The amplified effects of soil surface energy reflectance and conductance on soil-atmosphere heat fluxes can be harmful for leaf and berry physiology. Leaf/canopy temperature is a biophysical variable with both physiological and agronomic meaning. Improved comprehension of spatial and temporal dynamics of soil and leaf/canopy temperature (thermal microclimate) in irrigated vineyards can support improved crop and soil monitoring and management under more extreme and erratic climate conditions. In this work we propose a conceptual approach to integrate information on major soil-vine-atmosphere interactions under deficit irrigation. Ultimately a conceptual model based on temperature relations is proposed to support assessment of the impact of air and soil temperatures on canopy and berry temperatures, leaf senescence and gas exchange. This model may support Decision Support Systems (DSS) for canopy and soil management and irrigation scheduling in Mediterranean vineyards. In addition a set of temperatures (e.g. canopy, soil) are proposed to feed the conceptual models to support the DSS